Selenium prevents lipid peroxidation in liver and lung tissues of rats in acute swimming exercise - Akil, M.; Gurbuz, U.; Bicer, M.; Halifeoglu, I.; Baltaci, A.K.; Mogulkoc, R. (Comenius University, 2015)
Background: Selenium, which is critical for human health, is necessary for various metabolic processes, including thyroid hormone metabolism, protection against oxidative stress, and immune function. Objective: The present study aims to examine how selenium administration affects lipid peroxidation in liver and lung tissues of rats subjected to acute swimming exercise. Methods: The study included 32 Spraque-Dawley adult male rats divided into Group 1 (general control), Group 2 (selenium-administered), Group 3 (swimming), and Group 4 (selenium-administered swimming). MDA and GSH levels were determined in liver and lung tissues. Results: The highest MDA values in the liver and lung tissues were found in group 3 in the study. MDA value in group 4 was higher than those in groups 1 and 2. Group 4 had the highest liver and lung GSH levels. GSH levels in Group 3 were higher than those in groups 1 and 2. Conclusion: Results of the study indicate that acute swimming exercise causes lipid peroxidation in liver and lung tissues, while selenium administration prevents free radical formation by increasing antioxidant activity (Tab. 2, Ref. 26). Text in PDF www.elis.sk.
Keywords: Exercisef; Lipid peroxidation; Rat; Selenium